2022
DOI: 10.1097/sla.0000000000005619
|View full text |Cite
|
Sign up to set email alerts
|

An International Cohort Study of Prognosis Associated With Pathologically Complete Response Following Neoadjuvant Chemotherapy Versus Chemoradiotherapy of Surgical Treated Esophageal Adenocarcinoma

Abstract: Objective: To compare overall (OS) and recurrence-free survival (RFS) in esophageal adenocarcinoma patients with a pathologically complete response (pCR) following neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy (nCRT). Background: In the absence of survival differences in several prior studies comparing nCT with nCRT, the higher rate of pCR after nCRT has been suggested as reason to prefer this modality over nCT. Methods: An international cohort study included data from 8 high-volume cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…The subgroup analysis of operative approach may also support this hypothesis, with the direction of effect favoring improved outcomes among patients post transthoracic esophagectomy treated with nCT. Moreover, in patients achieving an R0 resection, OS was significantly improved following nCT as compared with nCRT (HR = 2.61), consistent with a recent multicenter observational data from Cools-Lartigue et al, 12 who demonstrated that 5-year recurrence-free survival was significantly improved in those who achieved pCR following nCT as compared with nCRT (HR = 1.70), with concomitant reductions in systemic recurrence (OR = 2.50). These data in a large population, we suggest, can inform modern multidisciplinary team decision-making, supporting a context-dependent tailored approach in the choice of neoadjuvant strategy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The subgroup analysis of operative approach may also support this hypothesis, with the direction of effect favoring improved outcomes among patients post transthoracic esophagectomy treated with nCT. Moreover, in patients achieving an R0 resection, OS was significantly improved following nCT as compared with nCRT (HR = 2.61), consistent with a recent multicenter observational data from Cools-Lartigue et al, 12 who demonstrated that 5-year recurrence-free survival was significantly improved in those who achieved pCR following nCT as compared with nCRT (HR = 1.70), with concomitant reductions in systemic recurrence (OR = 2.50). These data in a large population, we suggest, can inform modern multidisciplinary team decision-making, supporting a context-dependent tailored approach in the choice of neoadjuvant strategy.…”
Section: Discussionsupporting
confidence: 86%
“…Intriguingly, it is suggested that a pCR following nCT has a more favorable long-term outcome as compared with those with a pCR following nCRT. This highlights the relevance of how an integrated response at both local and systemic sites gives the maximum oncologic benefit, with the increasing evidence of the efficacy of adjuvant immunotherapy in selected patients with LAEC supporting this thesis 12 …”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, the mid-term survival outcomes described above are similar, if not marginally improved, to the outcomes described in other studies incorporating taxane based perioperative regimens 4,5 . Anecdotally, the overall survival of 100% at 3 years in patients with a pCR also compares favorably with similar cohorts of patients in whom pCR was also achieved 24 .…”
Section: Discussionmentioning
confidence: 81%
“…The long-term results of the POET trial [ 28 ] reported a trend to better overall survival after RCT, although our data, as long as previous long-term studies, do not confirm this finding [ 7 , 8 , 9 , 10 , 12 , 23 ]. Recently, patients with pCR after CT were reported to have better recurrence-free survival than those with pCR after RCT [ 29 ]. Moreover, it has to be kept in mind that radiation is no longer an option in the case of locoregional recurrence in patients already treated with RCT preoperatively.…”
Section: Discussionmentioning
confidence: 99%